2023
DOI: 10.5114/biolsport.2023.112972
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between vertical jump tests and ice-skating performance in junior Polish ice hockey players

Abstract: The aim of this study was to determine the relationships between vertical jumps (VJ) and various on-ice skating performances of junior ice hockey players (n = 19). The three modes of VJ or off-ice measures were countermovement jump with arm swing (CMJ), squat jump (SJ) and depth drop jump (DDJ). The on-ice skating performance was measured by the skating multistage aerobic test (SMAT), forward and backward acceleration test, top speed test, and repeated sprint ability (RSA) test. The relationships between the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In line with data of this study, Laakso & Secomb (14) measured how athletes with better 10–20 m sprint performance were able to generate greater concentric relative force in the CMJ with a strategy that maximized power output in a shorter period of time (RSImod). These data underscore the requirement that to achieve maximum sprint speed in skating, an athlete must maximize the force applied to the ice surface in the time available and optimize their stride frequency at the same time (8,14). Reactive strength index is often not considered in ice hockey performance diagnostics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with data of this study, Laakso & Secomb (14) measured how athletes with better 10–20 m sprint performance were able to generate greater concentric relative force in the CMJ with a strategy that maximized power output in a shorter period of time (RSImod). These data underscore the requirement that to achieve maximum sprint speed in skating, an athlete must maximize the force applied to the ice surface in the time available and optimize their stride frequency at the same time (8,14). Reactive strength index is often not considered in ice hockey performance diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…The data from this study indicate that reactive strength is not performance determining on the ice surface in skating. However, because a study with Polish junior athletes showed large correlations between reactive strength and skating performance ( r 2 = 0.38–0.64) (8), it is clear that further research is warranted. Future research should aim to determine whether such relationships are causal.…”
Section: Discussionmentioning
confidence: 99%
“…Vertical jumps (squat jumps, countermovement jumps, and free-arm countermovement jumps) were performed using the Optojump Next system (Microgate Italy, Bolzano, Italia). Jump height was calculated from the flight time, which has high reliability according to the intraclass correlation coefficient (ICC > 0.92) ( Gupta et al, 2022 ). Each type of the jump was performed in two sets of three consecutive jumps separated by a 5-min rest interval, and the best jump height was used for statistical analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The squat jump was performed from a starting position with 90° knee flexion held maximally for 2 s. During the squat jumps, participants were instructed to place their hands on their hips and bend at the knees, hips, and ankles. After participants stabilized in the starting position, the tester instructed them to jump as high as possible, keeping their hands on their hips and legs straight ( Gupta et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation